Suppose we have $$f(x) = a_n(x-x_1)(x-x_2)\cdots(x-x_n) = a_n \prod_{k=1}^n \left(x-x_k\right)$$

Then by Newton's identities we can write:

$$k e_k(x_1,\cdots,x_n) = \sum_{j=1}^{k-1} (-1)^{j-1} e_{k-j} (x_1,\cdots,x_n) p_{j}(x_1,\cdots,x_n) $$

where $e$ is an elementary symmetric function of the roots and $p$ is a power sum of the roots.

I've also stumbled across this link:


Which claims the $p_j$ can be expressed in terms of lower order power sums and coefficients $a_l$ of the original polynomial.

e.g. $$ \begin{split} a_n p_1 + a_{n-1} &= 0\\ a_n p_2 + a_{n-1}p_1 + 2 a_{n-2} &= 0 \end{split} $$

Is it possible to express a given power sum $p_j$ in terms of only coefficients of the polynomial and perhaps elementary symmetric functions such that no power sum terms are used?

Thank you.



You must log in to answer this question.

Browse other questions tagged .